Lycopene prevents adriamycin-induced testicular toxicity in rats - Ateşşahin, A; Türk, G; Karahan, İ; Yılmaz, S; Çeribaşı, Ao; Bulmuş, Ö (My University, 2006)
Objective: To investigate a possible protective role of lycopene on adriamycin (ADR)-induced spermiotoxicity using quantitative, biochemical and histopathological approaches. Design: Experimental study. Setting: Firat University Medical School, Experimental Research Centre, Elazig, Turkey. Animals: Twenty four Sprague Dawley rats (8-weeks old) Intervention(s): Adriamycin (10 mg kg 1) was intraperitoneally injected and lycopene (4 mg kg 1) was administered by gavage in corn oil. Main outcome measure(s): Reproductive organ weights were evaluated along with epididymal sperm concentration, motility and morphology. Testicular histological findings, oxidative status and plasma testosterone levels were also determined. Result(s): Lycopene ameliorated ADR-induced reductions in both testes and epididymis weights. ADR decreased sperm motility, increased total abnormal sperm rates, but epididymal sperm concentration was not changed compared to control. A marked normalization was achieved in sperm motility and morphology in pretreatment with lycopene. Although testosterone level was decreased in ADR group compared to control, no changes were observed in pretreatment group. An increase in malondialdehyde and a decrease reduced glutathione concentrations were detected in alone ADR group compared to control. Pretreatment with lycopene restored significantly malondialdehyde and reduced glutathione concentrations. ADR caused severe degenerative changes in germinative cells, atrophy in the diameter size of seminiferous tubules and germinative cell thickness. However, ADR-induced histopathological alterations were effectively reverted by pretreatment with lycopene. Conclusion(s): This study clearly indicates that ADR treatment markedly impaired testicular function and that pretreatment with lycopene might prevent this toxicity.
Likopen adriamisinin neden olduğu testiküler toksisiteyi önler
Makale - Yabancı Dilde Makale
Keywords: Lycopene adriamycin testicular function toxicity